COPYRIGHT PROTECTION SYSTEM AMONG CAPCUT CREATORS IN BANDA ACEH FROM THE PERSPECTIVE OF HAQ AL-IBTIKÂR AND LAW NUMBER 28 OF 2014 ON HAK CIPTA - Muchlas Rivaldi Mulka; Rahmat Efendy Al-Amin Siregar (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2025)
This article examines the copyright protection system among CapCut creators in Banda Aceh from the perspective of Haq al-Ibtikâr Law no. 28 of 2014 concerning copyright. Using qualitative research methods and a normative legal approach, the data were obtained through interviews and direct review of the accounts @raisyalmd, @ulfanabila, @mellyyusma, and @rayyaacantik. The results of the study show that there is a rise in the theft of photos which are used for personal gain, without considering in more depth the losses suffered by the photo owners themselves. Personal interests in achieving one's desires, even though the results of thoughts that have been manifested in written, printed, or other media, are considered property, is Haq Al-Ibtikâr. However, taking someone else's property is prohibited. Therefore, it is necessary to respect the work of others, who should ask for permission first before using it. This is because CapCut only provides reporting on its platform, as CapCut is not a distribution platform with automatic copyright protection for the images it uses. Unlike music, where the system automatically blocks or mutes the sound of the video. Therefore, protection depends on the photo owner. In this case, it is necessary to review the policy provided by CapCut regarding IPR regarding content uploaded to the CapCut application.